2000
DOI: 10.1123/wspaj.9.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Realities of Women’s Work Experiences in Coaching and Athletic Management

Abstract: This paper is an exploration of the multiple realities of women’s work experiences in coaching and athletic management positions. Eleven women who had previously coached or directed women’s athletics programs were interviewed using a semi-structured approach. Three general categories emerged from the data — Support, Gender Differences, and Change. The work experiences reflect problems the women encountered at work, how organizations can be empowering, and the impact empowered women can have on the social const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 0 publications
1
61
0
1
Order By: Relevance
“…Rankin-Wright, 2015;Allen and Shaw, 2009;Norman et al, 2014), and that many women coaches do not have faith or trust in those who are responsible for organising and leading their sport (e.g. Norman, 2008;2010;Allen and Shaw, 2013;Inglis et al, 2000). Our findings add that as well as 'race'…”
Section: Social Actualisationmentioning
confidence: 65%
“…Rankin-Wright, 2015;Allen and Shaw, 2009;Norman et al, 2014), and that many women coaches do not have faith or trust in those who are responsible for organising and leading their sport (e.g. Norman, 2008;2010;Allen and Shaw, 2013;Inglis et al, 2000). Our findings add that as well as 'race'…”
Section: Social Actualisationmentioning
confidence: 65%
“…Although Weinberg et al's sample (junior high, senior high, and collegiate male and female basketball players) was different than the sample used in this study (Division II collegiate male and female athletes from various sports), this comparison may mean that female athletes' perceptions of a female coach have not changed since 1984. Recent research has indicated that sport, and specifically collegiate athletics, may be a difficult work environment for female coaches (Inglis, Danylchuk, & Pastore, 2000;Kamphoff, in press;Theberge, 1993;Thorngren, 1990). The percentage of collegiate female head coaches of women's teams has steadily declined since the passage of Title IX and female coaches remain practically non-existent for men's teams (Acosta & Carpenter, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, such sacrifice may lead to pressure and strain within the coaching role, which may end in burnout and withdrawal (Inglis et al, 2000;Theberge, 1992;Weiss and Stevens, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%